Expectatoriality, Expectation, Expectations, Transexpectation - Dubatti, Jorge (2022)
In this article, from the Philosophy of Theater, a set of concepts is proposed to problematize the complexity of the action/event of expectation. Based on the Aristotelian distinction (Metaphysics) between close gender and specific difference, it is argued that "expectatoriality" is the condition that crosscuts various practices of expectation (artistic, social, trans-theatrical) founded on a common matrix of theatricality (understood as organization of the gaze of the other). It is also affirmed, from a pluralistic view, that there are "expectations" that imply different characteristics. Finally, we reflect on the pedagogies of expectatory events and their relationship with the knowledge of experience and time.